2014
DOI: 10.1002/jbio.201400047
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin spectroscopy as a new method of screening for increased CSF total protein during bacterial meningitis

Abstract: Bacterial meningitis is a disease of pronounced clinical significance, especially in the developing world. Immediate treatment with antibiotics is essential, and no single test can provide a conclusive diagnosis. It is well established that elevated total protein in cerebrospinal fluid (CSF) is associated with bacterial meningitis. Brillouin spectroscopy is a widely used optical technique for noninvasive determination of the elastic moduli of materials. We found that elevated protein levels in CSF alter the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…Recent research has also shown that mechanical stress may induce some or all of the biophysical effects associated with nanoporation [8][9][10] . The improvement of mechanical spectroscopies 11,12 in recent years should prove useful in the investigation of this mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has also shown that mechanical stress may induce some or all of the biophysical effects associated with nanoporation [8][9][10] . The improvement of mechanical spectroscopies 11,12 in recent years should prove useful in the investigation of this mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…However, weak signals are still difficult to detect in the presence of strong background. This becomes a significant issue when imaging biological tissues [26,27]. Scarcelli and Yun addressed these difficulties by introducing a multi-stage VIPA setup, which provides an additional 25 dB of the background suppression [23].…”
Section: Introductionmentioning
confidence: 99%
“…26 Without an equivalent confocal pinhole (e.g., without an SM¯ber), this broadening e®ect cannot be e±ciently suppressed. 8,27 In the speci¯c measurements shown in Figs. 2(a) and 2(c), the Brillouin line was broadened by 5 pixels (i.e., $400 MHz in Brillouin shift).…”
Section: Methodsmentioning
confidence: 99%
“…This becomes a signi¯cant issue when imaging turbid biological tissues. 8,22 This problem is further compounded when paired with imperfect optical setups, which are usually polluted with unwanted background noises and signal losses. Scarcelli and Yun addressed these di±culties by introducing a multi-stage VIPA setup, which provides an additional 25 dB of the background suppression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation